Effects of Teacher Educators’ Emotional Intelligence on their Teaching Practices - Maleeha Hammad, Samina Naseem (JELM, 2023)
Teacher educators play a significant role in preparing prospective teachers. They are not only responsible for teaching student-centered teaching practices (TPs) to prospective teachers, but also for modeling those practices in their classrooms. Research suggests that teachers who are emotionally intelligent tend to employ student-centered TPs in their classrooms. Using an inferential approach, this study aimed at finding out the influence of teacher educators’ emotional intelligence (EI) on their TPs. It was hypothesized that EI has no significant influence on teacher educators’ TPs. The data was collected by administrating an EI Questionnaire and TP Questionnaire survey. Using total population sampling technique, all teacher educators were selected as sample of the study from the institutions offering B. Ed (Hons.) Elementary Program in Rawalpindi and Islamabad. The regression analysis showed significant influence of EI on TPs’ of teacher educators. The paper also discusses the influencing and non- influencing competencies of EI. The study recommends professional development for teacher educators to upgrade and strengthen the knowledge about Emotional Intelligence and the teaching practices which are more student-centered – thus helping teacher educators to bridge the gap between theory and practice through modeling